Investment in transport and communication technology in a Cournot duopoly with trade - Luca Lambertini; Giampaolo Rossini (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2001)
We investigate the role of R&D investment in transport and communication (TCRD) in a Cournot duopoly with trade. Our analysis suggests that firms may invest in TCRD at reasonable levels of efficiency of TCRD even when they do not maximize their aggrerate payoffs, i.e., when the game ia s prisoner`s dilemma. As we consider countries of different size, it appears that for low levels of efficiency of TCRD only small countries invest. Welfare effects suggest that investing in TCRD is superior fot the country that understands it. The terns of trade improve as the foreign market gets larger and, in some cases, if the foreign firms invest in TCRD.
Keywords: 330